The Relationship between the Aquatic Extracts of the Moringa Oleifera Seeds and the Genetic Expression of (SAP5) Gene in Candida albicans Accompanying Cancer Patients - Majid kadhim Aboud Alshibly (Journal of Global Pharma Technology, 2017)
It has been detected gene expression using the Real – time technique for some Isolations Candida albicans before and during infection to cells epithelium, Ther esults be  high rate of gene expression (37.156 ±7.66049) to T2 treatment  and significantly difference at the level of the probability P ≤ 0.01 ,compared with the C treatment  that at a rate(1.040 ± 0.32229).As the use of an extract of the seeds of Moringa Oleifera In the concentration of 25% to assess its impact on the gene expression (SAP5) before and during infection yeast cells of epithelial and the results were reduced gene expression treatment T1 at a rate(0.074 ± 0.01542) comparison with the treatment C (1.040 ± 0.32229) and teams significantly at the level of the probability P ≤ 0.01, As for the T2 treatment was gene expression at a rate(37.156 ±7.66049) high Compared with T3 treatment in which gene expression dropped at a rate (19.565 ± 8.82162) and with a significant difference at the level of the probability of P ≤ 0.01. Keywords:  Moringa Oleifera, SAP5gene, C.albicans, Candidiasis, Real-time PCR.